Implementasi model Project Based Learning berbasis Etnomatematika untuk meningkatkan kemampuan literasi matematis - Fauzi, Ahmad; Yusuf, Yusfita; Koswara, Ucu (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2024)
This study was driven by the low mathematical literacy skills observed among junior high school students. To address this issue, a project-based learning model incorporating ethnomathematical elements was utilized as a strategy to enhance these skills. This study aims to find out which improvement in mathematical literacy skills is better between students who obtain a project-based learning model with ethnomathematical nuances and students who obtain a conventional learning model. This research is a quasi-experimental type, using a quantitative method with a non-equivalent control group design research design. The research population is all students of grade VIII MTs Al-Falaahiyah. With the purposive sampling technique, class VIII C was chosen as the experimental class that obtained the PjBL model with ethnomathematical nuances, and class VIII B as the control class that obtained the conventional learning model. Data were collected through mathematical literacy tests and analyzed quantitatively. The results of the gain index show that the improvement in mathematical literacy skills of the experimental class is higher than that of the control class. The results of the Mann Whitney U test at the 5% significance level showed that there was a difference in mathematical literacy ability between the experimental class and the control class. It can be concluded that the improvement of mathematical literacy skills of students who obtained a project-based learning model with ethnomathematical nuances is better than that of students who obtained a conventional learning model.